Genome-Wide Population Structure Analysis and Genetic Diversity Detection of Four Chinese Indigenous Duck Breeds from Fujian Province - Ruiyi Lin; Jiaquan Li; Yue Yang; Yinhua Yang; Jimin Chen; Fanglu Zhao; Tianfang Xiao (Animals, 2022)
The assessment of population genetic structure is the basis for understanding the genetic information of indigenous breeds and is important for the protection and management of indigenous breeds. However, the population genetic differentiation of many local breeds still remains unclear. Here, we performed a genome-wide comparative analysis of Jinding, Liancheng white, Putian black, and Shanma ducks based on the genomic sequences using RAD sequencing to understand their population structure and genetic diversity. The population parameters showed that there were obvious genetic differences among the four indigenous breeds, which were separated groups. Among them, Liancheng white and Shanma ducks may come from the same ancestor because the phylogenetic tree forms three tree trunks. In addition, during the runs of homozygosity (ROH), we found that the average inbreeding coefficient of Liancheng white and Putian black ducks was the lowest and the highest, respectively. Five genomic regions were considered to be the hotspots of autozygosity among these indigenous duck breeds, and the candidate genes involved a variety of potential variations, such as muscle growth, pigmentation, and neuroregulation. These findings provide insights into the further improvement and conservation of Fujian duck breeds.